2019
DOI: 10.1002/jcp.28871
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 4: A key player in Parkinson's disease

Abstract: Parkinson's disease (PD) is one of the most prevalent neurodegenerative diseases which occur in aged people worldwide. Given that a sequence of cellular and molecular mechanisms, including oxidative stresses, apoptosis, inflammatory pathways, microglia, astrocyte activation, and aquaporin 4 (AQP4) are associated with initiation and the progression of PD. AQP4 may affect various pathways (i.e., α-synuclein, inflammatory pathways, and microglia and astrocyte activation). Few reports have evaluated the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 105 publications
0
25
0
Order By: Relevance
“…Additional genes associated with mechanisms implicated in PD pathogenesis are also differentially expressed in T cells from PD_R subjects, including septin 5 (Son et al, 2005), the GDNF receptor (Sandmark et al, 2018), monoamine oxidase S, aquaporin (Tamtaji et al, 2019), LAMP3 (Liu et al, 2011) which has also been associated with REM sleep disorder (a risk factor for PD (Mufti et al, 2021)), polo-like kinase 1 (Mbefo et al, 2010), and myeloperoxidase (Maki et al, 2019). Most of these genes have been found previously to be expressed in neurons, but here we show for the first time DE of these genes in peripheral cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additional genes associated with mechanisms implicated in PD pathogenesis are also differentially expressed in T cells from PD_R subjects, including septin 5 (Son et al, 2005), the GDNF receptor (Sandmark et al, 2018), monoamine oxidase S, aquaporin (Tamtaji et al, 2019), LAMP3 (Liu et al, 2011) which has also been associated with REM sleep disorder (a risk factor for PD (Mufti et al, 2021)), polo-like kinase 1 (Mbefo et al, 2010), and myeloperoxidase (Maki et al, 2019). Most of these genes have been found previously to be expressed in neurons, but here we show for the first time DE of these genes in peripheral cells.…”
Section: Discussionmentioning
confidence: 99%
“…AQP4 has been implicated in the pathophysiology of many neurological (23,(27)(28)(29)(30)(31)(32) and psychiatric (33)(34)(35) diseases. In a previous study, AQP4 gene polymorphisms were examined in children with febrile seizures and revealed no association with the rs1058424 AT genotype or rs3763043 CT genotype SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the regulation of water permeability by astrocytic water channels, aquaporin-4 (AQP4), in the BBB plays an important role in several physiological conditions in the CNS. Recently, the expression and regulation of AQP4 have been studied in several pathological situations, suggesting that AQP4 participates in the onset and progression of PD [145]. Xue et al [146] reported that AQP4-deficient mice displayed significantly stronger microglial inflammatory responses and a markedly greater loss of dopaminergic neurons after MPTP injection.…”
Section: Astrocyte Dysfunction In Parkinsonismmentioning
confidence: 99%